Development of fouling resistant nanofiltration membrane for microbial biomass harvesting - Lai, Yanjun (Nanyang Technological University, 2022)
Microbial organisms have long been utilized to remove nutrients from waste streams at high efficiency, while also producing biomass which can be used as fuel or further processed into other valuable resources. Among commonly applied microbial biomass harvesting technologies, membrane separation is the most fascinating technique granted by high recovery rate and stability. One of the key challenges in biomass filtration process is membrane fouling. Nanofiltration (NF) membrane was proposed as a solution to suppress membrane fouling by preventing pore plugging phenomenon. In this study, outer-selective NF hollow fiber membrane suitable for biomass concentration was prepared via layer-by-layer (LBL) deposition technique. The effect of membrane coating process parameters on membrane properties were explored, including poly-cation type, supporting electrolyte concentration and crosslinker concentration. LBL-modified NF membranes were characterized in terms of pure water permeability (PWP), salt rejection rate, and molecular weight cut-off (MWCO). To investigate the fouling resistance of NF membranes, membrane fouling tests were conducted by using aerobic heterotrophic bacteria (AHB) suspension cultured with food waste stream from local beverage production factory as the feed. The performance of LBL-modified NF membrane in AHB biomass concentration process was also assessed. The performance of the NF membrane in biomass concentration was evaluated in terms of water flux and recovery of water permeability. The current study demonstrated the NF membrane exhibited high fouling resistance in microbial biomass filtration process. However, further improvement in membrane performance could be achieved through a better module design.